Comparison of high temperature resistance in two buckwheat species Fagopyrum esculentum and Fagopyrum tataricum - Aubert, Lauranne; Konrádová, Daniela; Kebbas, Salima; Barris, Selma; Quinet, Muriel (Journal of plant physiology, 2020)
In the context of ongoing climate change, expected temperature rise may significantly limit plant growth and productivity of crop species. In this study, we investigated the effects of a sub-optimal temperature on buckwheat, a pseudocereal known for its nutraceutical advantages. Two buckwheat species differing by their reproduction method, namely Fagopyrum esculentum and Fagopyrum tataricum were grown at 21 °C and 27 °C in growth chambers. High temperature increased leaf production mainly in F. tataricum but decreased leaf area in both species. Water and photosynthesis-related parameters were affected by high temperature but our results suggested that although transpiration rate was increased, adaptive mechanisms were developed to limit the negative impact on photosynthesis. High temperature mainly affected the reproductive stage. It delayed flowering time but boosted inflorescence and flower production. Nevertheless, flower and seed abortions were observed in both species at 27 °C. Regarding flower fertility, heat affected more the female stage than the male stage and reduced the stigma receptivity. Pollen production increased with temperature in F. esculentum while it decreased in F. tataricum. Such discrepancy could be related to the self-incompatibility of F. esculentum. Both species increased their antioxidant production under high temperature to limit oxidative stress and antioxidant capacity was higher in the inflorescences than in the leaves. Total flavonoid content was particularly increased in the leaves of F. esculentum and in the inflorescences of F. tataricum. Altogether, our results showed that even if high temperature may negatively affect reproduction in buckwheat, it improves its antioxidant content.
Keywords: rozmnožování; antioxidancia; Fagopyrum; Antioxidant; Tartary buckwheat; Common buckwheat; Heat; druhová specificita; Hot Temperature; Reproduction; Photosynthesis; Flower fertility; vysoká teplota; termotolerance; Thermotolerance; Species Specificity; Antioxidants